PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (STUDI PADA PT. CENDANA PUTRA LESTARI, CABANG SUMATERA BARAT) - Noverina Dwinawangsari; Okta Karneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the effect of work motivation on employee performance through job satisfaction as an intervening variable at PT. Sandalwood Putra Lestari. The independent variable is work motivation (X) and the intermediary or mediating variable is job satisfaction (Z). while the dependent variable is employee performance (Y). This study uses a questionnaire with measurements using a Likert scale. Linear regression analysis technique with the help of software SmartPls 3.2.6. the population in this study were 94 employees of PT. Cendana Putra Lestari. From the results of the tests conducted, it shows that work motivation has a positive and significant effect on job satisfaction, work motivation has a positive and significant effect on employee performance, job satisfaction has a positive and significant effect on employee performance and work motivation has a positive and significant effect on employee performance through job satisfaction as a variable. intervention.Keywords: Work Motivation, Employee Performance, Job Satisfaction